Relacje interlingwalne między niemieckimi derywatami z -ung i ich odpowiednikami w języku polskim na przykładzie tekstu specjalistycznego - Kubacki, Artur Dariusz (Investigationes Linguisticae, 2009)
The aim of the paper is to present and examine translation strategies used to find Polish equivalents of German deverbative derivatives suffixed with -ung which are not components of compounds or nominal groups. All the derived forms suffixed with -ung which appeared separately in a German legal and economic text have been subject to analysis. The author discusses in detail the structure of German morphological forms and then he compares it with the structure of their Polish equivalents. As a result, he distinguishes such translation techniques as calquing, a change within the formal structure of a derivative, a change in derivational bases or their number and the use of loanwords.